2000
DOI: 10.1016/s0378-1097(00)00131-2
|View full text |Cite
|
Sign up to set email alerts
|

A consensus Porphyromonas gingivalis promoter sequence

Abstract: We have determined the transcription start points (tsp) for recently identified Porphyromonas gingivalis W50 genes, kgp, rgpA, rgpB (formerly designated prtK, prtR, and prtRII respectively), fetB and the mcmAB operon. Alignment of the DNA upstream of these tsp and those from the literature has enabled us to identify consensus sequences that may represent a P. gingivalis promoter. There is a potential 310 hexamer sequence, 5P-TATATT-3P centred on average at 310/11 nt which is repeated at 319/20 nt and an upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…RT-PCR data indicated that these two genes are cotranscribed (data not shown). The region upstream of the putative 5-methylthioadenosine nucleosidase-S-adenosylhomocysteine nucleosidase gene contained prokaryote promoter consensus sequences identified using the Promoter Predictions search tool of the Berkeley Drosophila Genome Project (http://www-.fruitfly.org) and by visual comparison with a set of predicted P. gingivalis consensus promoter sequences (20). Thus, transcription of luxS may require the promoter of the upstream ORF.…”
Section: Resultsmentioning
confidence: 99%
“…RT-PCR data indicated that these two genes are cotranscribed (data not shown). The region upstream of the putative 5-methylthioadenosine nucleosidase-S-adenosylhomocysteine nucleosidase gene contained prokaryote promoter consensus sequences identified using the Promoter Predictions search tool of the Berkeley Drosophila Genome Project (http://www-.fruitfly.org) and by visual comparison with a set of predicted P. gingivalis consensus promoter sequences (20). Thus, transcription of luxS may require the promoter of the upstream ORF.…”
Section: Resultsmentioning
confidence: 99%
“…Primer extension analysis of ihtB showed that the transcription start point is 267 bases upstream from the methionine translation start codon (21). A nearly perfect invert repeat sequence was identified 45 nucleotides downstream from the stop codon, between bases 1391 and 1439 (AGAGCACTtATCGAGAAga aggacttgccgatTTCTCGATgAGTGCTCT).…”
Section: Resultsmentioning
confidence: 99%
“…The most extensively characterized UP element is an ATrich sequence located between Ϫ40 and Ϫ60 in the rrnB P1 promoter of E. coli (19,20), which stimulates promoter activity at least 30-fold (19). UP-like elements found upstream of Bacteroidetes promoters have been recognized in B. fragilis (1) and P. gingivalis (27). A genome-wide survey of putative promoters in members of the phylum Bacteroidetes also showed that UPlike sequences occur at ϳ20 bp upstream of the Ϫ33 promoter motifs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This is in spite of the ubiquitous distribution of members of the phylum Bacteroidetes (6, 14, 30, 31); their importance as pathogens of fish (15, 42), birds (54), and humans (7); and their roles in transforming high-molecularweight carbon compounds in soil and aquatic environments (14). Most research on gene regulation in this phylum has targeted Bacteroides (4,11,32,49,55,57) and, to a lesser extent, Porphyromonas (27,43,57,60). Early examination of the transcriptional signals in Bacteroides fragilis indicated that its promoters exhibited features distinct from those of proteobacteria (4, 55).…”
mentioning
confidence: 99%